KELUHAN KELELAHAN MATA PADA PEKERJA PENGGUNA KOMPUTER DI PERUSAHAAN TRAVEL DI KOLAKA RAYA - Sunyanti Sunyanti (IDENTIFIKASI, 2019)
Eye fatigue in computer users can occur because it works by seeing and reading near in a long time. Such conditions can decrease accuracy and alertness. Also can reduce the health condition of workers can even cause accidents work. Therefore, this research is done to know the complaints of fatigue on workers computer users in the Travel company in Kolaka Raya. This research is quantitative research with cross-sectional study design. This research sample is 30 computer users in the Travel company in Kolaka Raya. Data retrieval is performed by spreading questionnaires and measuring visibility between eyes and computer screen. Univariate is done using a proportion value to explain the description of eye fatigue complaints and relationships in computer users with eye fatigue, bivariate analysis is performed with a Chi-square test (X2) with a 10% significance rate. The results showed that 22 respondents or 73.3% had eye fatigue complaints. The most complaints that are in the natural worker are headaches as much as (53.3%). Based on the results of a statistical test it is known that variables associated with eye fatigue complaints are variable duration work (P-value = 0.03). To reduce the risk of eye fatigue complaints on computer users in suggesting the need to do maintenance and maintenance to the quality of lighting and cleaning of the lamp periodically for 6 months. There is a need to socialize with the right resting time so as not to use the rest time to use the computer.